Post-revanchist cities?. Issue 7 (9th August 2019) - DeVerteuil, Geoff
ABSTRACT: This intervention focuses on how national-level rhetoric aimed at impugning "others" has thrived of late, but how concomitantly 1990s-style urban revanchism has faded in cities that were once punitive crucibles against the homeless. Using Los Angeles as case study, I argue that the recent trend has been to grudgingly support the homeless, increasingly via taxpayer initiatives, leading to a potential but stymied post-revanchist city. If the spirit of revanchism remains, it is through the persistent NIMBY opposition to housing the homeless.